Effects of defensive pressure on basketball shooting performance - Csataljay, G.; James, N.; Hughes, M.; Dancs, H. (International Journal of Performance Analysis in Sport, 2013)
Reasons behind successful team performance were explained through analysing the effects of defensive pressure on basketball shooting performance. Team success, shooting efficiency and defensive opposition were analysed from 3344 shooting attempts with Wilcoxon signed ranks tests, Friedman tests and odds ratio calculations. Results of the analysis identified significant differences between winners and losers for close 2 point and 3 point shooting percentages. The increased level of defensive pressure had influential effect on the shooting performance and the game outcome. It was concluded that winning teams achieved more effective shooting percentages as the consequence of better team cooperation, because players could work out more opened scoring opportunities without any active defensive presence. The other occasion of the higher shooting percentages was the level of defensive performance because winners more times forced their opponent to try under maximal defensive pressure. After all, perhaps the most important difference between winning and losing teams was that winners could exploit their scoring opportunities more effectively, not only without defensive opposition but also from the hardest situations under high level of defensive pressure also.